Developing a dichlorosalicylaldehyde-derived fluorescent probe for monitoring glutathione in a cellular pulmonary ventilation model - Zhou, Xiao; Zhang, Lei; Lao, Yuwen; Zhou, Bin; Zhu, Zhongquan (Frontiers in Chemistry, 2025)
Herein, a fluorescent probe, DSNBD-GSH, was developed from dichlorosalicylaldehyde to monitor glutathione (GSH) in a cellular pulmonary ventilation model. Both the normoxia and hypoxia conditions were evaluated. DSNBD-GSH responded to GSH in a dosage-dependent manner with a fluorescence signal at 478 nm under the excitation of 365 nm. The solution tests indicated that DSNBD-GSH had relatively high sensitivity for GSH, and the photophysical properties were stable in various conditions. Other advantages included rapid response, high selectivity, and low cytotoxicity. Most significantly, monitoring the GSH level in both hypoxia and recovery status allows for visualization of ventilation-related redox changes. This work highlights a referenceable case for improving the pulmonary ventilation approach during the perioperative period.